The effect of elemene on lung adenocarcinoma A549 cell radiosensitivity and elucidation of its mechanism (Clinics, 2015)
OBJECTIVE: To investigate the effect of elemene on the radiosensitivity of A549 cells and its possible molecular mechanism. METHODS: Apoptosis of A549 cells was detected by flow cytometry and fluorescence microscopy. The effect of double-strand break (DSB) damage repair in A549 cells was evaluated using the neutral comet assay. Protein expression levels were detected using western blotting, and the correlation between protein levels was analyzed. RESULTS: Elemene exhibited a radiosensitizing effect on A549 cells. The level of apoptosis induced by elemene combined with radiation was significantly greater (p